“Evaluación fisicoquímica del maíz amarillo duro (zea mays) Tratado bajo fertilización orgánica e inorgánica a dos niveles de nitrógeno en el valle del chira – Piura - Saavedra Paredes, Carmela (2005)
The present work has as objective to improve the characteristic physicalchemical of the grain of hard yellow com (zea mays) treaties low organic and inorganic fertilization at two nitrogen levels in the valley of the Chira - Piura. For the installation of the work the statistical desígn was used by divíded parcels being used until the cultural evaluations of the cultivation, having 3 treatments for each fertilization source and four repetítions. For the evaluation physicalchemical a design was used totally at random in block (DBCA) with factorial arrangement of 2x3 with four repetitions. In both cases he/she was carried out the variance analysis and the test from Duncan to the O. 05% of probability. The influence was evaluated in the improvements of the conditions of the cultivation and the matter prevails of the corn that you/they were treated under the application of fertilizers organic and inorganic nitrogen given to different dose (high = T1 = 240 Kg. of N/Ha. , low = T2 = 180 Kg. of N/Ha. and witness = T3 · = O Kg of N/Ha. ), carrying out a permanent control in each stage of the cultivation and allowing this way to evaluate the development and the behavior of the cLiltivF!tion 19wers these fertilizatíon parameters until arriving to the crop. Of · the obtained .· ré.sults you concludes that discharge existed high differs significant among the treatments for the different doses and source of fertilization nitrogen, showing in the: a Plant height, standing out the T1 from the organic fertilization to high dose with a value 235 cm. and the inorganic fertilization to high dose with a value of 245cm. Maintaining the direct proportional in that manifested in the height of ear insert with values of 130cm. for the organic fertilization to high dose and of 135 cm. for the inorganic fertilization to high dose. ti When evaluating the yield of the grain the best yields they are shown in the organic and inorganic fertilization to high dose with a value of 11 458 Kg. /Ha. and the lowest yields in the witness of the inorganic fertilization with 2 604 Kg. /Ha. , being demonstrated that the organic fertilization is one of the best options to obtain a better yield and good weight of the grain also attributed to the floor type. a In the physical evaluation was carried out by means of different methods for each evaluation, for the evaluation biometric of the grain the Vernier was used and a better characteristic was obtained in the grains of corn yellow hard treaties low organic fertilization to high dose with the following values 13. 50 mm of thickness, 8. 20 mm wide, 5. 50 mm of thickness, 102. 70 mm2 surface and 594. 00 mm3 of volume; in the evaluation density and hardness, it was determinad by the method of apparent density of grains and the resistance method to the break respectively which doesn't show significant difference. a The chemical evaluation carried out by means of the method of analysis proximal, that allowed us to measure the humidity, protein, fat, fiber, ash, carbohydrates and starch, where it was observad existed high differs significant, rescuing the values obtained in the content of proteins wíth a ·value of 12. 8% and carbohydrates with 68. 1 % treaties with fertilization organic nitrogen to high dose. The contents of fat, fiber, ash and humidity .don't.show significant difference. . . Finally :the treatment with organic fertilization to high dose had better results in . ' .' . ' almdst.all.th~ carried out evaluations, mainly in the height and strenuousness of the plant, oontainéd protein, of starch and in the evaluation biometric of the . . grain; presenting ·.a better size, uniformity and improvements in the nutritional content arid protein of the grain.